Two new species of Sericosura Fry & Hedgpeth, 1969 (Arthropoda: Pycnogonida: Ammotheidae) from a hydrothermal vent on the East Pacific Rise - Wang, Jianjia; Lin, Rongcheng; Bamber, Roger N.; Huang, Dingyong (Zootaxa, 2013)
Between 17th October and 9th November 2009, the third leg of the Chinese DY115-21 cruise on board the R/V Dayangy-ihao, confirmed two new hydrothermal fields near the equatorial East Pacific Rise. Five pycnogonid specimens were ob-tained by deep-sea TV-grab from one of the new hydrothermal vents named ’Precious Stone Mountain’ at 1.22°N 101.49°W. These specimens belonged to two new species of the obligately-vent-associated pycnogonid genus Sericosura. Three female specimens represent the new species Sericosura gemmaemonsis with large body size. One male and one fe-male were of the second new species, Sericosura dentatus; the male specimen has a mid-dorsal femoral cement-gland-tube, like that of Sericosura dissita, while the female specimen has more finely-denticulate spines on the oviger strigilis than any other species of the genus.